2013
DOI: 10.1371/journal.pone.0063543
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Ultrasound Backscattered Statistics and the Concentration of Fatty Droplets in Livers: An Animal Study

Abstract: Ultrasound grayscale B-mode imaging is the most frequently used modality for examining fatty liver. Different concentrations and arrangements of fatty droplets in the liver may produce different statistical distributions of ultrasound backscatter signals, which may be treated as a useful clue for assessing the stage of fatty liver. To verify this point, we investigate the relationship between changes in backscattered statistics and the concentration of fatty droplets in the liver. Fatty liver was induced in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…SL = 3 was used because the side length of the window corresponding to three times the pulse length of the transducer enables a stable estimation of the Nakagami parameter13152529. The Nakagami parameters and the entropy values of benign and malignant tumors were shown in the box plots (expressed by the median and interquartile range, IQR) for comparisons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SL = 3 was used because the side length of the window corresponding to three times the pulse length of the transducer enables a stable estimation of the Nakagami parameter13152529. The Nakagami parameters and the entropy values of benign and malignant tumors were shown in the box plots (expressed by the median and interquartile range, IQR) for comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers reported potential applications of ultrasound Nakagami parametric imaging in visualizing backscattered statistics for quantifying the properties of tissues, such as in breast tumor classification1314, liver fibrosis detection in rats1516, radiotherapy evaluation17, cataract detection18, skin characterization19, vascular flow analysis20, thermal ablation monitoring21, and characterizing the structural anisotropy in the myocardium22. Various research groups demonstrated that the Nakagami image visualizes scatterer arrangements and concentrations and complements the conventional B-scan for tissue characterization.…”
mentioning
confidence: 99%
“…The second method uses statistical distributions to model the echo amplitude distribution for a more accurate statistical analysis. This concept has been realized using statistical models, such as K [26] and Nakagami distributions [27,28], indicating that the echo amplitude distribution varies from pre-Rayleigh to Rayleigh with the formation of fatty liver.…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, non-model-based parameters that can be calculated using any type of data irrespective of the data distribution are suggested as alternatives for characterizing tissues. Among non-model-based statistical parameters, entropy has been shown to correlate with the parameters of the statistical models and the envelope statistics [33], which is a useful clue for characterizing fatty liver [27,28]. Recall that Shannon established information theory and defined entropy as a measure of information uncertainty [34].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as the Nakagami parameter varies from 0 to 1, the echo amplitude distribution changes from a pre-Rayleigh to a Rayleigh distribution; a Nakagami parameter of >1 represents that the echo amplitude distribution conforms to a post-Rayleigh distribution22. Recently, the Nakagami parameter has been widely used in soft-tissue characterization of, for example, cataracts26, blood27, liver2829, breast30, and thrombus31. The Nakagami parameter is also used in modeling the echo amplitude distribution of bony tissues3233.…”
mentioning
confidence: 99%